An analysis of the Indian retail market: Growth challenges, opportunities, and forecast to 2027 - Kumar, Sandeep; Bakshi, Sweta (YAYASAN MITRA PERSADA NUSANTARA, 2024)
This research paper delves into the Indian retail market, analyzing its growth trajectory, identifying key challenges, exploring emerging opportunities, and providing a forecast up to 2027. Through a comprehensive examination of market trends, consumer behavior, regulatory frameworks, and technological advancements, this paper aims to offer valuable insights for stakeholders seeking to navigate and capitalize on the dynamic Indian retail landscape.